The value of an interdisciplinary education for prospective law students - Drake, Ian J. (Journal of Interdisciplinary Studies in Education, 2013)
Undergraduate pre-law education must prepare prospective law students for the challenges of law school and the law school admissions process. Although law school does not require a prerequisite course of study, it is my contention that the optimal undergraduate preparation consists of interdisciplinary liberal arts education. Such a pedagogical approach allows for students to understand law in the context of society and its practice beyond the theoretical fundamentals taught in most law schools. Many law school faculty favor interdisciplinary education in law school and law admissions officials stress liberal arts education for undergraduates. Accordingly, the optimal pre-law undergraduate education should take into account both interdisciplinarity and liberal arts approaches to law. I highlight some programs providing such undergraduate education.